Jornalismo e discurso sobre si: a construção do ethos jornalístico na carta do editor de Zero Hora e Gaúcha ZH - Teixeira, Leandra Cruber (2022)
Immersed in a scenario of crises in journalism and constant reconfigurations of professional practice, the research thematizes journalism and the construction of self-- images from the Editor's Letter of Zero Hora (ZH) and GaúchaZH (GZH), media that belong to the RBS Group and share the so called Integrated Editorial Office. With the intention of problematizing and reflecting on the profession, the research efforts focus on understanding how journalism has approached itself considering the scenario of transformations in the field (CHARRON; BONVILLE, 2016) and , also, of crises in journalism (CHRISTOFOLETTI, 2019). The background of the research is the unification of Rádio Gaúcha and Zero Hora, media of large audience and circulation in the South. The merger of the radio and the printed newspaper did not happen only in the digital sphere, it was a material and structural change. Thus, from changes both in the internal organization, production routines and journalistic products, there is an emphasis on a discourse that speaks about itself, as is the space called t he Editor's Letter. In these letters, the editorinchief or the editorinchief of the integrated newsroom talks about the journalistic productions of ZH, Rádio Gaúcha, and the GZH platform. Fifty the Editor's Letter published between Janusix editions of ary 2019 and December 2020 are analyzed. The general objective is to understand the construction of the journalistic ethos from the identification of the nuclei of meaning related to the values and functions of journalism, relating them to the context of t ransformations and crises. Among the specific objectives are to identify how the selfreferential discourse contributes to the construction of ethos and map the predominant meanings about values and functions of journalism in the Editor's Letter. Thus, bas ed on the principle that the set of dispositions, perceptions and values that journalists have of themselves and the world build the journalistic ethos, the research problem can be summarized in the following statement: from the condition of identity of th e media instance that integrates the communication contract (CHARAUDEAU, 2006), which nuclei of meaning make up the marks of journalistic ethos (ORLANDI, 2005; MAINGUENEAU, 2008) present in the Editor's Letters of ZH and GZH? From the analysis of 104 Discu rsive Sequences, we identified 23 meaning nuclei that integrate two major Discursive Formations: the first one points to a traditional vision of the values and functions of Journalism; the second one gathers SDs that present a limited vision of the crises and the transformations of Journalism. Thus, among the conclusions, we highlight that, despite a discourse that emphasizes transformations, adaptations and innovations in journalism, from a character similar to that of manuals and prescriptions, the reaffi rmation of an identity makes us believe that the journalistic ethos built by the Editor's Letter refers to traditional values in an attempt to stabilize certain certain notions about journalism.